MicroRNAs as multifaceted regulators and therapeutic targets in ulcerative colitis - Wang, Xuerui; Jiang, Nan; Yin, Weixiang; Cui, Xiaofeng (Frontiers in Immunology, 2025)
Ulcerative colitis (UC) is a chronic inflammatory bowel disease characterized by mucosal barrier disruption, immune dysregulation, and gut microbiota imbalance. MicroRNAs (miRNAs), small non-coding regulators of gene expression, have emerged as pivotal modulators of UC pathogenesis. By orchestrating epithelial cell apoptosis, tight junction integrity, and mucin secretion, miRNAs such as miR-223, miR-151-5p, and miR-429 contribute to barrier dysfunction. Additionally, miRNAs shape the innate and adaptive immune responses by influencing macrophage polarization, dendritic cell maturation, and T cell subset differentiation, including Th17/Treg and Th1/Th2 balance. Specific miRNAs further modulate gut microbial composition and host-microbe interactions. Clinically, circulating miRNAs serve as promising non-invasive biomarkers for disease diagnosis, activity monitoring, and therapeutic response prediction. Therapeutically, miRNA mimics and inhibitors have shown efficacy in early-phase clinical trials, offering a novel strategy beyond current biologics. This review summarizes recent mechanistic insights and translational advances, underscoring the multifaceted roles of miRNAs in UC and their potential to inform precision diagnostics and targeted therapies.